Combination of Laserpunktur Technology and Pepaya Seed Extract (Carica papaya L.) as a Potential of Fasciolosis Therapy in Cow - Erfan Andrianto Aritonang; Firdaus Hasibuan (Jurnal Peternakan (Jurnal of Animal Science), 2020)
Fasciolosis is a strategic parasitic disease that can reduce productivity in cattle and dairy. Papaya seeds are medicinal herbs used as anthemeltics. In general, herbal medicine takes a long time to cure. The purpose of this paper is to provide a study of the combination of laserpunktur technology and papaya seed extract as a potential therapy for fasciolosis in cattle. Papaya seed extract as a natural anthemeltic works synergistically with laserpunktur technology which will provide energy stimulation to the gastrointestinal organs and liver of cattle infected with fasciolosis. The synergy of papaya seed extract increases the metabolism of the drug in the liver more smoothly so that the drug is able to eliminate Fasciola sp. maximally. The writing method is the study of literature combined with ideas in the form of laserpunktur technology. The parameters of successful administration of papaya seed extract in fasciolosis patients are in terms of the number of worm eggs per gram of stool, average weight gain, and body condition score (BCS). The laserpunktur method is performed at points ST-36 (Sao-San-Li), CV-4 (Guan-Yuan), LIV-3 (Tai-Chong) with a single irradiation wave size of 1 joule / point. The distance between the laserpunktur machine and cowhide is 10 cm. The duration of laserpunktur therapy is 2 x 30 minutes / week. The combination of laserpunktur and papaya seed extract as a therapy allows the acceleration of healing time of fasciolosis in cattle. The combination of laserpunktur technology and papaya seed extract is expected to be an innovative therapeutic treatment of fasciolosis in effective cows.